Esthetic Rehabilitation with Combined All-Ceramic Applications: A Case Report - Guzelce, Elifnur; Karacaer, Ozgul (The Journal of Dentists, 2017)
The first choice for anterior rehabilitation has been metal-free materials due to their successful esthetic results. Dentists and dental technicians today require materials that offer high strength, outstanding esthetics and efficient productivity. IPS e-max lithium disilicate can now be processed with CAD/CAM technology or traditionally pressed or contemporarily. Thus, its strength and versatility, the material used for the following practice anterior/posterior crowns, anterior three-unit bridgework (press only), inlays/onlays, veneers, thin veneers, implant restorations, telescopic crowns. The case presented in this report illustrates the rehabilitation of maxillary anterior teeth with IPS e-max press ceramic bridge and laminate veneers.